Evaluation report of the workshop on the use of the updated ECLAC Disaster Assessment Methodology : Tortola, British Virgin Islands - NU. CEPAL. Sede Subregional para el Caribe (ECLAC, Subregional Headquarters for the Caribbean, 2019)
Introduction. -- General information. -- Summary of key outcomes of the training course. -- Summary of evaluation. -- Conclusions.